2019
DOI: 10.1088/1361-6528/ab2282
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in near-field nanolithography using light interactions with colloidal particles: from nanospheres to three-dimensional nanostructures

Abstract: The advance of nanotechnology is firmly rooted in the development of cost-effective, versatile, and easily accessible nanofabrication techniques. The ability to pattern complex two-dimensional and three-dimensional nanostructured materials are particularly desirable, since they can have novel physical properties that are not found in bulk materials. This review article will report recent progress in utilizing self-assembly of colloidal particles for nanolithography. In these techniques, the near-field interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 206 publications
0
38
0
Order By: Relevance
“…It is therefore important to examine how the nanosphere assembly yield translates to the 3D lithography yield. For positive photoresist, the positions below the spheres upon normal illumination will be holes due to the near-field focusing effect 55 . Therefore, the exposure dose can be estimated by measuring the hole diameter using top-view SEM imaging.…”
Section: Characterization Of the Lithography Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to examine how the nanosphere assembly yield translates to the 3D lithography yield. For positive photoresist, the positions below the spheres upon normal illumination will be holes due to the near-field focusing effect 55 . Therefore, the exposure dose can be estimated by measuring the hole diameter using top-view SEM imaging.…”
Section: Characterization Of the Lithography Yieldmentioning
confidence: 99%
“…Therefore, precise quantitative metrology of the assembly yield rate over a large area is challenging. In recent work, various groups have demonstrated that colloidal nanospheres can be used as a near-field optical element for nanolithography to create 3D periodic nanostructures [53][54][55][56][57][58] , nanovolcanoes 59,60 , and hierarchical structures 61 . However, in these proof-of-concept demonstrations, the colloidal assembly and lithography were performed manually within a limited area.…”
Section: Introductionmentioning
confidence: 99%
“…227 This is especially the case when the microsphere is embedded in an atomic force microscopy (AFM) cantilever because the precise control of the AFM cantilever translates into precise positioning and movement of the generated PNJs. 228,229 See the cantilever-based nanolithography in Fig. 9(b).…”
Section: Deep-subwavelength Fwhm and Neareld Effect Of Pnjsmentioning
confidence: 99%
“…231,232 We recommend ref. 228 to our readers for more information regarding microsphere-based nanofabrication. Optical data storage.…”
Section: Deep-subwavelength Fwhm and Neareld Effect Of Pnjsmentioning
confidence: 99%
“…Nanospheres lithography [16,17] is a fabrication process with reference to the selfassembly of nanocolloids. A lithography mask is first prepared by submerging the substrate in the nanocolloids suspension.…”
Section: Introductionmentioning
confidence: 99%